Municipal solid waste management of Zanzibar: current practice, the challenges and the future - Ally, Biubwa; Syed Ismail, Sharifah Norkhadijah; Rasdi, Irniza (Excellent Publishers, 2014)
This paper present the current status of municipal solid waste management (MSWM)system in Zanzibar municipality.The study provides an overview with focus on different aspects of MSWM such as generation, collection and disposal, recycling, identifying the main problems and limitations that hinder improvement in the current municipal solid waste management practices and suggestion on the measures to be taken to alleviate these problems. The information was obtained from Zanzibar Municipal Council (ZMC) personnel with varying responsibilities within the system, relevant stakeholders and representative community members using questionnaire.